2022
DOI: 10.1002/sd.2383
|View full text |Cite
|
Sign up to set email alerts
|

Can nuclear energy technology budgets pave the way for a transition toward low‐carbon economy: Insights from the United Kingdom

Abstract: The energy resources of the economies play a critical role in reaching the 2030 and 2050 decarbonization targets. In this respect, research and development budgets for nuclear energy (NRD), which constitutes one-fifth of the current energy resources in the United Kingdom, can be a step in the transition to a low-carbon economy. However, the current literature neglects the impact of NRD on environmental quality for the United Kingdom. Thus, this paper explores the impact of NRD on CO 2 in the United Kingdom by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Green process research identified by several scholars has shown that organizational initiatives in process improvement are connected to upgraded manufacturing firm performance (Jacobs et al 2015). Caglar's (2022) study highlighted that green environmental processes improve financial development and environmental quality. Numerous scholars have investigated that government regulation and stakeholder pressure trigger manufacturing firms to improve the production process (Guo et al 2019).…”
Section: Green Environmental Processmentioning
confidence: 99%
“…Green process research identified by several scholars has shown that organizational initiatives in process improvement are connected to upgraded manufacturing firm performance (Jacobs et al 2015). Caglar's (2022) study highlighted that green environmental processes improve financial development and environmental quality. Numerous scholars have investigated that government regulation and stakeholder pressure trigger manufacturing firms to improve the production process (Guo et al 2019).…”
Section: Green Environmental Processmentioning
confidence: 99%
“…Understanding the links between environmental degradation and SDGs is essential for developing holistic and effective strategies for sustainable development. The SDGs are a set of 17 global goals that aim to address various social, economic, and environmental challenges to achieve sustainable development by 2030 [3,4]. SDG 7 aims to ensure access to affordable, reliable, sustainable, and modern energy for all.…”
Section: Introductionmentioning
confidence: 99%
“…The current decade's prevalent challenge is maintaining the balance between economic growth and carbon emission reduction [ 6 ]. Foreign direct investment is a critical player in economic growth [ 7 ]. FDI is equally important for developing and developed countries to boost the scale of development, and continuous efforts and strategies are designed to attract FDI [ 8 ].…”
Section: Introductionmentioning
confidence: 99%